Prevalence of disordered eating attitudes in young adults - Vlachakis, Dimitrios; Vlachakis, Chrisanthy (PeerJ PrePrints, 2014)
Objective. The objective of this study was to assess the prevalence of disordered eating and the dietary patterns of young adult female students. Method. 226 young female first and second year students were randomly recruited. The EAT-26 questionnaire was used to measure disordered eating, and the State Trait Anxiety Inventory tool (STAI) to assess anxiety levels. Results. The prevalence of disordered eating (DE group) was quite high and matched previous reported percentages for this age population (18%). DE students showed significantly lower energy intake compared to control group (CON) (1471 ± 357 vs. 1690 ± 563, kcals). Conclusion. Young adult female students show increased tendency towards disordered or restricted eating behaviours. Preventive intervention concerning the negative behaviours may be beneficial for all college students more so to those suffering from anxiety.
Keywords: eating disorder attitude; intelligence; anxiety; Emotional